2020
DOI: 10.3390/en13030635
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Process Integration Options for Joule-Cycle and Conventional Heat Pumps

Abstract: To date, research on heat pumps (HP) has mainly focused on vapour compression heat pumps (VCHP), transcritical heat pumps (TCHP), absorption heat pumps, and their heat integration with processes. Few studies have considered the Joule cycle heat pump (JCHP), which raises several questions. What are the characteristics and specifics of these different heat pumps? How are they different when they integrate with the processes? For different processes, which heat pump is more appropriate? To address these questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Since the presented cost parity curves only depend on the temperature lift ∆T lift , the assumption of constant sink tem-perature T h,out and economic boundary conditions as well as the statistical uncertainty of the COP modelling slightly falsifies the critical temperature lift as target value. The novel targeting method using METD also meets the requirements of Fu and Gundersen [16] and Gai et al [19] for realistic modelling of the temperature change on the process sink side. The conventional approach according to Stampfli et al [11] used a storage-based HRL (cf.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Since the presented cost parity curves only depend on the temperature lift ∆T lift , the assumption of constant sink tem-perature T h,out and economic boundary conditions as well as the statistical uncertainty of the COP modelling slightly falsifies the critical temperature lift as target value. The novel targeting method using METD also meets the requirements of Fu and Gundersen [16] and Gai et al [19] for realistic modelling of the temperature change on the process sink side. The conventional approach according to Stampfli et al [11] used a storage-based HRL (cf.…”
Section: Discussionmentioning
confidence: 83%
“…The Exergy Per total annual Cost criterion (EPC) was proposed by Wang et al [18] to select HPs based on their economic and thermodynamic performance. Gai et al [19] emphasised the importance of matching the correct HP type with the thermal requirement of each process. While, for example, transcritical HPs are better suited for sinks with large temperature changes and sources with small, vapour compression HPs are better suited for near-constant constant sink and source temperatures.…”
Section: Heat Pump Integration Methodsmentioning
confidence: 99%
“…In the last paper on this topic, the authors Gai et al [104] reported on the "Critical Analysis of Process Integration Options for Joule-Cycle and Conventional Heat Pumps". They examined different types of heat pumps and their heat integration into the process.…”
Section: Heat Integration and Heat Transfermentioning
confidence: 99%
“…However, other cycles can be advantageous depending on the temperature profile or the plant where they are used. In their analysis of different industrial heat consumers, Gai et al [8] found that sometimes the transcritical, Brayton or Rankine cycle is optimal depending on the process under consideration. In particular, Brayton-based heat pumps may offer more versatility in design and operability when processes characterized by large temperature glides are considered, as they use single-phase operating fluid and exchange sensible heat with the temperature sink and source [3].…”
Section: Introductionmentioning
confidence: 99%